(2z-9)(4-z)=0

Simple and best practice solution for (2z-9)(4-z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2z-9)(4-z)=0 equation:


Simplifying
(2z + -9)(4 + -1z) = 0

Reorder the terms:
(-9 + 2z)(4 + -1z) = 0

Multiply (-9 + 2z) * (4 + -1z)
(-9(4 + -1z) + 2z * (4 + -1z)) = 0
((4 * -9 + -1z * -9) + 2z * (4 + -1z)) = 0
((-36 + 9z) + 2z * (4 + -1z)) = 0
(-36 + 9z + (4 * 2z + -1z * 2z)) = 0
(-36 + 9z + (8z + -2z2)) = 0

Combine like terms: 9z + 8z = 17z
(-36 + 17z + -2z2) = 0

Solving
-36 + 17z + -2z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-9 + 2z)(4 + -1z) = 0

Subproblem 1

Set the factor '(-9 + 2z)' equal to zero and attempt to solve: Simplifying -9 + 2z = 0 Solving -9 + 2z = 0 Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2z = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 2z = 0 + 9 2z = 0 + 9 Combine like terms: 0 + 9 = 9 2z = 9 Divide each side by '2'. z = 4.5 Simplifying z = 4.5

Subproblem 2

Set the factor '(4 + -1z)' equal to zero and attempt to solve: Simplifying 4 + -1z = 0 Solving 4 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1z = 0 + -4 -1z = 0 + -4 Combine like terms: 0 + -4 = -4 -1z = -4 Divide each side by '-1'. z = 4 Simplifying z = 4

Solution

z = {4.5, 4}

See similar equations:

| K/6=8/15 | | t^2-14t-15=0 | | 3x/4-5/3=x/6 | | 13/15=X/35 | | 3x/3-4x/5=2/15 | | 3(2k-5)-7x=4x+20 | | 2(h-4)=h+2 | | 800+16x=720+21 | | 14+y=-11 | | 2/3t-1=3 | | 3x+15=25-4x | | 12=-2n | | (5/8)3.(2/5)2 | | 5b^2-30b+25=0 | | -1/3=2/7x-1/2 | | 139/10 | | 9z=5z+6 | | 3-9x=y | | -(5/6)/(15/16) | | 3×1/8 | | m+2+m+-5=15 | | 5+x+3=x+5+3 | | 25-17=3(x-2) | | 20*log(x)=3 | | 4.(4/7)2.(-3/4)3 | | (X+1)+9=x+(1+9) | | 20log(x)=3 | | (10x-13)(6x+1)= | | 1/3x-15=-1 | | .15*x=2.95 | | -3(a+1)=57 | | 4(y-2)=76 |

Equations solver categories